(untitled) (American Journal of Islam and Society, 2005)
The theme of this year’s event, “Muslims in North America: Accomplishments, Challenges, and the Road Ahead,” was a public proclamation that North American Muslims are focusing on the future. One highlight was the presence of Undersecretary of State for Public Diplomacy Karen Hughes, who met with heads of Muslim American organizations on the grounds that she needed their advice to help her reach out to the wider Muslim world. Overall, the convention focused on advancing values of the family, community, compassion, and justice; the workshops addressed community building, organizing politically, promoting civil rights, opposing Islamophobia, sharing Islam, and promoting interfaith understanding. The conference was inaugurated by the leaders of ISNA’s constituent organizations and leaders of other faiths. Bob Edgar (secretary general, National Council of Churches), set the tone: “If you want to walk fast, walk alone. If you want to walk far, walk together!” Muhammad Nur Abdullah (president, ISNA) spoke of such ISNA accomplishments as the imam and chaplain training services and empowering Muslim youths. The inaugural session was addressed by Khurshid A. Qureshi (president, AMSE) Rafik Beekun (president, AMSS), Rehana Kausar (president, IMANA), Mohammad Sheibani (president, MSA), and co-chairs Omar Siddiqi and Kulsoom Salman (both of MSA-National). Ingrid Mattson (vice president, ISNA; director, Islamic chaplaincy; and professor, Islamic studies and Christian-Muslim relations, Hartford Seminary), Abdul-Malik Mujahid (president, Council of Islamic Organizations of Greater Chicago), Bob Edgar (secretary general, National Council of Churches), and Rick Ufford-Chase (chair of the moderator of the 216th General Assembly of the Presbyterian Church [USA]). The ISNA Dr. Mahboob Khan Community Service Award was presented to Ilyas Ba-Yunus, a founding member of MSA who helped establish ISNA and served as its first president. A respected sociologist, he is the author of several studies related to Muslim life in America. Former Malaysian deputy prime minister Anwar Ibrahim, the keynote speaker at the Community Service Recognition luncheon, expressed his gratitude for ISNA’s role in securing his release after the charges brought against him by former prime minister Mahathir Muhammad failed the court test. In keeping with a now 3-year-old tradition, Anwar received an award recognizing his contribution to democracy, civil society, and social justice ...